Procesos participativos y tecnologías abiertas en la agricultura familiar : el aporte del diseño industrial para fortalecer los procesos de innovación - Chierchie, Laura (2022)
Family farming is the main mode of agricultural production on the planet. In the world there are about 1,500 million peasants, smallholders and small producers. However, they occupy only 20 percent of the available land. Despite inhabiting the territory in a few hectares, they produce 56 percent of the food consumed on the planet. Conventional agriculture and agribusiness, as the dominant pathways of innovation, present serious challenges and incompatibilities with the context of family farmers: has a large impact on the natural environment and causes environmental degradation, concentrates production and displaces indigenous rural populations. Many innovations have removed producer families from the creative process by developing artifacts that supposedly accommodate their activity, largely ignoring their empirical contributions and wishes. Some, abandoned their traditional models and adopted exogenous technology but have suffered great changes and failures in their production schemes. Conventional innovation has failed to develop specific consistent solutions for family farming.\nIn view of these problems, what happens when open and participatory models are applied in the design of technologies, machines and artifacts? The research aims to determine how open design is implemented and what benefits it presents. The purpose of the study is to analyze how the opening process occurs in participatory projects for the development and implementation of open technologies in the field of family agriculture at the national level.\nFor this, after mapping existing cases of participatory development of international artifacts, four technological development projects are analyzed in the national field where designers, manufacturers, researchers and producer families participate. How are open technologies generated and implemented? What is participation in the process like? What learnings, knowledge and challenges yield by implementing open models? What potentialities and limitations does this development model have? The analysis made it possible to formulate and describe open and participatory design modalities that respond to experiences currently implemented, helping to identify appropriate openness and participation strategies.\nThe research presents as a guiding idea that open technological development processes present benefits in solving problems since they solve complex problems with few resources and low-cost, use the collective intelligence of those involved, accelerate the innovation cycle in relation to conventional innovation models and provide the possibility of generating designs that are adaptable to various contexts. However, despite these potentialities, there are also difficulties, obstacles and limitations. Which are they? How do the participants deal with them? The generated analysis allows us to think of open technologies and participatory processes as an alternative model of innovation in view of the challenges of agriculture, where the design discipline has a strategic and essential role in this type of process.